(3YbhO GdJLGQI GdOhdjIs - (3gTGe Ydj(B, (3UGObs ((3GdGScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2007)
(3eYGjjQ OhdjI GdYbO GdOhdj, GdfXQjI GdTNUjI hGadGJ GdYbO GdOhdj ef Mce GdbGfhf(B: (3GdfXQjI GdTNUjI hGfOeGL bGfhf GdGOGQI aj GdYbO, GdTNUjI dOi bVGA GdJMcje, GdfXQj GdehVhYjI hNVhY GdYbO GdOhdj dMce GdbGfhf(B: (3NVhY GdYbO GdOhdj dMce GdbGfhf habG defgL GdJfGRd, NVhY GdYbO GdOhdj dMce GdbGfhf habG ddefgL GdeHGTQs
(3HHdjhZQGajG(B: (3U(B.1079-1114s
Keywords: (3GdGOGQIs; (3GdJLGQI GdNGQLjIs; (3GdYbhOs